Library and information communications technology for enhancing teaching, learning and research in human kinetics education in Nigeria (2017)
This paper explores the role of the library and modern Information Communications and Technologies (ICT) in promoting teaching, learning and research (TLR) in Human Kinetics Education in Nigeria. It shows the importance of this area of study not just to national but also to human development. The methodologies for TLR are shown to be dynamic depending on the constant changes taking place in the discipline. Curriculum change reflects the infusion of ICT into the discipline which subsequently affects its pedagogy and library collections. The paper also identifies the constraints to proper library and ICT integration to education, nay, Human Kinetics Education in a developing economy as in Nigeria.